How valuable is information and communication technology? A study of emerging economy enterprises - Luo, Yadong; Bu, J. (Pergamon, 2016)
Anchored at the knowledge management perspective, we address how information and communication technology (ICT) improves the productivity of emerging economy enterprises. We present the logic that ICT enhances firm performance because it is an important channel or facilitator of effective knowledge sharing and knowledge integration. We further argue that the conditions characterizing an emerging economy (i.e., a country's economic development) and emerging economy businesses (i.e., internationalization and quality assurance) would affect the extent to which ICT contributes to knowledge management, and thus to firm performance. Our hierarchical linear modeling analysis of 6236 firms from 27 emerging economies lends support to our arguments and predictions, suggesting that ICT is a critical investment that generates satisfactory returns for emerging economy enterprises, yet this investment-return relationship is further contingent upon the macro- and micro-level conditions facing these enterprises. ICT actually adds more value to productivity when a focal emerging economy is less economically developed, and when a focal firm reaches foreign markets or its quality control and assurance is superior.